The elements of financial structure and their impact on the market value of the firm economic. Case study of the debts of Saidal Group ( 1999-2014) - Shailia, Nabila; Bouktir, Jabar (Milev Journal of Research and Studies, 2017)
This study aimed at clarifying the impact of the financial structure of the institution on its market value (market price per share). The approaches and theories differed in the interpretation of the relationship of the financial structure to the value of the market institution. There are supporters who supported the impact of the financial structure on the market value of the institution. This study found that the financial structure could be used to explain the changes in the market price of the industrial share of the industrial compound by 40.09%. It also revealed an inverse relation between the ratio of total debts to private equity and market price of the share the complex.